2017
DOI: 10.1002/alr.21964
|View full text |Cite
|
Sign up to set email alerts
|

Defining the minimal clinically important difference for olfactory outcomes in the surgical treatment of chronic rhinosinusitis

Abstract: BACKGROUND Olfactory dysfunction is a common and defining symptom of chronic rhinosinusitis (CRS). Many measures of olfactory dysfunction in CRS are limited by scoring criteria defined within general populations with interpretations of statistical significance to infer clinically meaningful improvement. This investigation defines a minimal clinically important difference (MCID) for the Brief Smell Identification Test (BSIT) in CRS patients electing endoscopic sinus surgery (ESS). METHODS A multi-center cohor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 43 publications
0
29
0
Order By: Relevance
“…In our analysis health utility as measured by the SF-6D did not provide sufficient diagnostic utility to perform a robust anchor-based analysis, in contrast to prior work by our group investigating the Brief Smell Identification Test (BSIT), in which a successful anchor-based approach was used to confirm the distribution-based findings. 30 Nevertheless, having a frame of reference to interpret the clinical significance of changes in PROM scores has significant utility in outcomes research, and the previously discussed agreement of our mean scores with widely accepted anchor-based measures of the MCID lends credibility to the distribution approach in this particular case and offers a useful benchmark to interpret domain score changes.…”
Section: Discussionmentioning
confidence: 64%
“…In our analysis health utility as measured by the SF-6D did not provide sufficient diagnostic utility to perform a robust anchor-based analysis, in contrast to prior work by our group investigating the Brief Smell Identification Test (BSIT), in which a successful anchor-based approach was used to confirm the distribution-based findings. 30 Nevertheless, having a frame of reference to interpret the clinical significance of changes in PROM scores has significant utility in outcomes research, and the previously discussed agreement of our mean scores with widely accepted anchor-based measures of the MCID lends credibility to the distribution approach in this particular case and offers a useful benchmark to interpret domain score changes.…”
Section: Discussionmentioning
confidence: 64%
“…Although the lack of statistical significance may be due to the inadequate power of studies included in the meta‐analysis, even a statistically significant change of −1.03 on the UPSIT and −0.77 on the CCSIT would be unlikely to be clinically significant. Previous studies have defined the minimal clinically important difference of both scores to be about a 10% change in the UPSIT and a change of 1 on the CCSIT …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have defined the minimal clinically important difference of both scores to be about a 10% change in the UPSIT and a change of 1 on the CCSIT. 13,46,48 Results from studies that compare olfaction outcomes with or without harvesting of NSF have been conflicting. A previous comment by Greig et al suggested that NSF elevation likely leads to impairment in objective measures of olfaction, whereas ESBS without elevation of NSF only leads to transient reduction in olfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Third, these reported MCID values are reflective of current standards of care for both medical and surgical therapy, and may not hold true if significant shifts in either treatment modality occur in the future, such as increased use of biologics for CRS or similar targeted therapies . Fourth, an anchor‐based determination of the MCID was not able to be performed in this study, which could assist in independently confirming the distribution‐based findings . Fifth, CAMT was left to the discretion of each individual practitioner by design, thus introducing potential heterogeneity to the medical treatment arm.…”
Section: Discussionmentioning
confidence: 92%
“…11 Fourth, an anchor-based determination of the MCID was not able to be performed in this study, which could assist in independently confirming the distribution-based findings. 25 Fifth, CAMT was left to the discretion of each individual practitioner by design, thus introducing potential heterogeneity to the medical treatment arm. This was chosen to allow providers the flexibility to select treatments as the clinical picture of the patient evolved, but it does limit generalizability compared to the surgical cohort, where there is more standardization of treatment.…”
Section: Discussionmentioning
confidence: 99%